A choice of realization strategy of the new project based on variables of possible technical, economic and organizational solutions - Yu. V. Krivolutsky (Путеводитель предпринимателя)
Development of feasible and effective management decisions as a task of optimal choice of some system parameters and their following realization influences significantly the main goals of the companies and defines its success in a competition. The article contains the statement of theoretical material and practical examples of the development of management decisions, models and methods are exploited in a multicriterial environment.